Population pharmacokinetics of regorafenib in solid tumours: Exposure in clinical practice considering enterohepatic circulation and food intake. Issue 12 (10th June 2020) - Keunecke, Anne; Hoefman, Sven; Drenth, Henk‐Jan; Zisowsky, Jochen; Cleton, Adriaan; Ploeger, Bart A.
Abstract : Aim: Regorafenib is an oral multikinase inhibitor with clinical efficacy in a range of advanced solid tumours. A population pharmacokinetic (PK) model was developed to evaluate the variability of the PK of regorafenib and its pharmacologically active metabolites M‐2 and M‐5 in solid tumours. Methods: The model was initially developed using densely sampled phase 1 data and information on food intake to incorporate enterohepatic circulation (EHC) that was identified to considerably contribute to the PK of regorafenib. This was then applied to sparsely sampled data from four phase 3 studies in patients with advanced solid tumours. The need for exact food intake data to estimate individual drug exposure was evaluated. Results: By incorporating EHC, the model adequately described the PK profiles of regorafenib, M‐2 and M‐5 after single and multiple doses in patients from phase 1 studies. Individual exposure in phase 3 studies was adequately described based on assumptions on the time and frequency of food intake, although exact food intake data are recommended to improve the estimation. Covariate analysis identified sex and body mass index (BMI) as impacting exposure to regorafenib, and sex as strongly impacting exposure to M‐2 and M‐5 (also influenced by the BMI effect on parent regorafenib in the joint model developed); however, these factors accounted for a small portion of the overall variability in exposure. Conclusions: The adequate description of regorafenib PK after multiple dosing requires the incorporation of EHC. Neither single nor combined covariates predicted exposures that would warrant a priori regorafenib dose adjustment.